A new method to determine 3D joint loading within lower extremities in snowboarding - Krüger, A.; McAlpine, P.; Borrani, F.; Edelmann-Nusser, J. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
NTRODUCTION: To reduce the risk of equipment related injuries in snowboarding, the development of enhanced snowboard equipment is considered in literature. Therefore, it is essential to understand the biomechanics of snowboarding especially with regard to ankle and knee joint loading. In the biomechanical literature only a few studies are available that have focused on the determination of joint loading within the lower extremities in snowboarding (Klous, 2007; McAlpine, 2010). However, these studies are limited to the analysis in a restricted capture volume due to the use of optical video based systems. To overcome this restriction the purpose of this study was to develop a method to determine net joint moments within the lower extremities in snowboarding for complete measurement runs.